VIDEO “MANOLA” (AMAN DI SEKOLAH) ON KNOWLEDGE AND ATTITUDES TO PREVENT COVID-19 TRANSMISSION IN PRIMARY SCHOOL STUDENTS - Utami Dewi; Nurul Aini Suria Saputri (Bajang Institute, 2021)
Children are one of the vulnerable groups to Covid-19 transmission because they have not been able to understand health protocols properly. Schools are at risk for an increase of Covid-19 cases when they reopen, this is evidenced by the increase in the number of school transmission cases from 2% to 23% in June 2020, to 70% in July 2020 and then to 90% in September 2020. This research was aimed to determine the effect of the “MANOLA” video on the knowledge and attitude of preventing the transmission of Covid-19 in primary school students. This research was a quasi-experimental type with one group pretest posttest design. The research was carried out at Primary School of 002 Tanjungpinang Timur. The population of this research were all fifth-grade students. Based on the calculation of the sample size, the number of samples was 33 respondents. The sampling technique in this research used non-probability sampling- purposive sampling. The data were analyzed using the Parametric Paired Sample T-test. The results showed that the average knowledge of students increased by 1.12 with a p value of 0.001 and the average attitude increased by 1.73 after being given an intervention in the form of a video “MANOLA” with a p value of 0.000. This research concluded that the video “MANOLA” can effectively increase knowledge and attitudes to prevent transmission of Covid 19 in primary school students because it attracts attention and interest so it can be easily understood. It is expected that this “MANOLA” video can be recommended as a method of health education for primary school students.